2015
DOI: 10.1016/j.rbmo.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Implication of sperm chromosomal abnormalities in recurrent abortion and multiple implantation failure

Abstract: Currently, some infertility treatment centres provide sperm karyotype analysis, although the impact of sperm chromosomal abnormalities on fertility is not yet fully understood. Several studies using fluorescence in-situ hybridization (FISH) to analyse sperm chromosomal constitution discovered that the incidence of aneuploidy is increased in individuals with a history of repeated abortion or implantation failure and is even higher in cases of oligoasthenoteratozoospermia (OAT), abnormal somatic karyotype or in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Additionally, the included trials showed high quality and precision. Other studies (Caseiro et al, 2015;Giorlandino et al, 1998;Lou et al, 2013;Rosenbusch et al, 1991) were mostly consistent with our current findings. These studies showed that the incidence of aneuploidy was increased in individuals with a history of repeated abortion.…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, the included trials showed high quality and precision. Other studies (Caseiro et al, 2015;Giorlandino et al, 1998;Lou et al, 2013;Rosenbusch et al, 1991) were mostly consistent with our current findings. These studies showed that the incidence of aneuploidy was increased in individuals with a history of repeated abortion.…”
Section: Discussionsupporting
confidence: 94%
“…SA is the most frequently occurring pregnancy disorder and is a serious threat to women's health (23). SA has been reported to be associated with several risk factors, including endocrine disorders, anatomic deformation, immunodeficiency and chromosomal abnormalities (24)(25)(26)(27). However, other risk factors and underlying molecular mechanisms of SA still need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In reproduction, telomeres may play an important role in chromosome pairing during meiosis (Bekaert, Derradji, & Baatout, ; de La Roche Saint‐André, ). Alterations at this level could cause segregation problems and a higher rate of sperm aneuploidy, apoptosis and lower sperm count (Perrin et al., ; Templado, Donate, Giraldo, Bosch, & Estop, ), which are features directly associated with infertility, miscarriages and implantation failure (Caseiro et al., ; Neusser et al., ).…”
Section: Discussionmentioning
confidence: 99%